What do we know about hallux valgus pathogenesis? : Review of the different theories - Ferreyra, Martín; Núñez-Samper , Mariano; Viladot, Ramón; Ruiz, Javier; Isidro, Albert; Ibañez, Luis (Journal of the Foot & Ankle, 2020)
Objective: This work performs a critical review of the different causes described to explain the etiopathogenesis of hallux valgus. Methods: The authors divide the causal factors into two groups: extrinsic and intrinsic factors. In the first group, footwear and mechanical overload caused by different causes such as ballet, trauma, long walks, obesity, etc., should be considered. In the second group we include a series of factors: constitutional ones, such as heredity, sex and age; anatomical aspects, among which we must highlight the morphology and obliquity of the metatarsocuneiform joint; hypermobility of the first ray; metatarsus primus varus; muscle function; and atavism. Results: Hallux valgus probably has a multifactorial etiology whose triggering factor is unknown at the moment. Conclusion: If we know the etiopathogenesis of a deformity, in this case hallux valgus, we can perform a treatment as early and effective as possible. Level of Evidence V; Therapeutic Studies; Expert Opinion.